Effectiveness of Forms of Legal Protection for Journalists in carrying out their journalistic duties - Syahril Abdullah (Universitas Negeri Gorontalo, 2019)
The series of cases that attack journalists in carrying out their duties shows that the journalist profession is vulnerable to actions that will harm and threaten the life of every journalist in carrying out their journalistic duties. Protection measures for every citizen are the responsibility of the state. Once the importance of the benefits that will be felt by the public from the work of journalists is inversely proportional to efforts to protect journalists. Based on this, the purpose of this study is to examine the forms of legal protection and the inhibiting factors in protecting journalists who are carrying out their duties. This study examines the subject matter in a juridical-empirical way using a legal approach and a sociological approach by conducting direct interviews with parties related to the subject matter. The results of the research authors obtain answers to existing problems, that the forms of protection that are carried out are utilizing regulatory protection regulated in Indonesian legislation and international agreements, as well as the forms of protection provided by professional journalists' organizations based on journalistic ethics guidelines and journalist professional organization guidelines. This form of protection is experiencing obstacles, namely obstacles in the law enforcement process against legal processes carried out against journalists, obstacles that are focused on individual journalists related to the professionalism of the press personnel, as well as obstacles experienced by professional organizations that cannot reach the increasing number of journalists. and growing in number.